Characterization and antioxidant activities of acidic polysaccharides from Gynostemma pentaphyllum (Thunb.) Markino. (20th August 2015) - Li, Bo; Zhang, Xiaoyu; Wang, Mingzhu; Jiao, Lili
Highlights: Three acid polysaccharides were isolated from Gynostemma pentaphyllum (Thunb.) Markino. GPA1, GPA2, and GPA3 were heteropolysaccharides with various molecular properties. GPA3 possessed better antioxidant activity in vitro than GPA1 and GPA2. GPA3 could be explored as novel antioxidants in functional foods and medicine. Abstract: Three acid polysaccharides obtained from Gynostemma pentaphyllum (Thunb.) Markino (named as GPA1, GPA2 and GPA3) using combination of water extraction, ion-exchange and gel permeation chromatography were subjected to composition analysis and valuated for the antioxidant activity. The sugar content of GPA1, GPA2 and GPA3 were 54.55%, 85.70% and 91.34%, respectively. Monosaccharide analysis showed that GPA1, GPA2 and GPA3 were all composed of Man, Rha, GlcA, GalA, Glc, Gal, Ara and Fuc, besides, GPA2 and GPA3 also contained Xyl. The molecular weight of GPA1, GPA2 and GPA3 were 19.6 kDa, 10.6 kDa and 6.7 kDa, respectively. In vitro antioxidant assay, GPA1, GPA2 and GPA3 could scavenge 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical and hydroxyl radical, chelate ferrous ion and reduce ferric ion. The antioxidant activities of GPA3 were stronger than those of GPA1 and GPA2, suggesting that GPA3 has significant potential as a natural antioxidant agent.